Offloading of diabetic foot wounds using Amit Jain’s offloading system: an experience of 23 cases - Dath, Roshan; Rao, U. Venkatkrishna; Kumar, Kishore; Kumar, Harish; Kumar, Suresh (International Surgery Journal, 2017)
Background: It is a well-known fact that around 15% of patients with diabetes are likely to be affected by foot ulcers during their lifetime. The aim of this study was to evaluate and analyze Amit Jain’s offloading system used in diabetic foot wounds. Methods: A cross-sectional, retrospective study was done at 3 centres namely Brindhavvan Areion Hospital, Synergy Centre for Diabetes and South City hospital in Bangalore, India. The study period was for 1 year from April 2016 to March 2017. Results: 23 cases were included in the study. 16 patients (69.57%) had right foot involved whereas 7 patients (30.43%) had left foot involved. Majority of the patients had foot problems located at forefoot (86.96%). The most common condition where Amit Jain’s offloading was used was in trophic ulcer (61%). In 22 patients (95.65%), the microcellular rubber and ethyl vinyl acetate combination was used whereas in one patient (4.35%), 7 mm of single layered EVA was used. 9 patients (39.13%) had their wounds healed within 8 weeks whereas 11 patients (47.83%) had their wounds healed within 8-16 weeks. Conclusions: Amit Jain’s offloading device is a new offloading device that can be effectively used as an alternative to felted foam. It is based on deflective technique just like felted foam. In this series, 86.98% of the wounds had healed by 16 weeks with this new offloading device. The Amit Jain’s offloading device, which has a scientific rationale based on the deflective offloading as well as usage of visco-elastic material that is accepted worldwide, produces effective wound healing without any complication and without inhibiting patient’s mobility. Amit Jain’s offloading is a level one recommendation for diabetic foot wounds.